An Analysis and Guidelines on Developing Classroom Research Competency for Early Childhood Teachers under Local Administrative Organization, Pathum Thani Province - Pantuworakul , Kullachat; Nuansri, Mesa (Journal of Modern Learning Development, 2022)
This research aims to 1) analyze the causes of problems to improve classroom research competency, and 2) propose ways to improve classroom research competency of early childhood teacher. The target groups were 10 experts in education by using purposive selection method. The instrument used in guidelines on focus-group questions. The data were analyzed using content analysis. The research results revealed 1. The most important causes of problems to improve classroom research competency of early childhood teachers in terms of 1) knowledge about defining classroom research problems included a misunderstanding of classroom research problem analysis, 2) skills in data analysis and presentation included an inadequate understanding of research methodology in education, and 3) attitude towards personality and motivation included heavy burdens of early childhood teachers. 2. Guidelines for improving classroom research competency of early childhood teachers classified by degrees of essentials could be purposed as follows: 1) three ways to improve data analysis and data presentation are to (1) assess knowledge and skills of the teachers, (2) establish a mentoring system, and (3) provide practice-oriented training; 2) three ways to improve the knowledge about defining classroom research problems are to (1) provide practice-oriented training, (2) prepare classroom research manuals for early childhood teachers, and (3) encourage teacher training institutions to focus on conducting researches to solve classroom problems; and 3) six ways to improve the attitude towards personality and motivation are to (1) encourage school administrators to clearly define roles and assign tasks to early childhood teachers, (2) create the organization management systems, (3) provide the school with sufficient personnel, (4) rais awareness and understanding of classroom research methodology, (5) boost morale as well as give moral support to early childhood teachers, and (6) create an understanding that research is part of their teaching and learning